Ileus Management International (IMAGINE): protocol for a multicentre, observational study of ileus after colorectal surgery. (3rd January 2018) - ,
Abstract: Aim: The management of postoperative ileus following colorectal surgery remains controversial. It is the commonest complication after elective colorectal resection and is associated with an increased incidence of postoperative adverse events. The prevention and management of postoperative ileus remains unstandardized. This study aims to describe an international profile of gastrointestinal recovery after colorectal surgery and will assess the role of non‐steroidal anti‐inflammatory drugs, when used as postoperative analgesia, in expediting the return of gastrointestinal function. Methods: A multicentre, student‐ and trainee‐led, prospective cohort study will be conducted across both Europe and Australasia. Adult patients undergoing elective colorectal resection during 2‐week data collection periods between January and April 2018 will be included. A site‐specific questionnaire will capture compliance to Enhanced Recovery after Surgery components at participating centres. The primary outcome is time to gastrointestinal recovery, measured using a composite outcome of bowel function and oral tolerance. The impact of non‐steroidal anti‐inflammatory drugs on gastrointestinal recovery will be evaluated along with safety data with respect to anastomotic leak, acute kidney injury and complications within 30 days of surgery. Discussion: This protocol describes the methodology of an international, observational assessment of gastrointestinal recovery after colorectal surgery. It discusses key challenges and describes how the results will impact on future investigation. The study will be conducted across a large student‐ and trainee‐led collaborative network, with prospective quality assurance and data validation strategies.